Women’s Empowerment in Agrifood Governance (WEAGov) assessment framework insights from the India pilot study - Ragasa, Catherine; Kyle, Jordan; Yasmin, Sabina; Pande, Harshita; Sharma, Aanshi; Basu, Sampurna; Najjar, Dina (International Food Policy Research Institute, 2024)
Women’s equal participation and leadership in political and public life can boost a country’s long-term economic growth, foster social inclusion, and help countries reach the 2030 Sustainable Development Goals (SDGs). Beyond these important outcomes, women’s inclusion in public life is a basic human right: Women deserve a role in making decisions, controlling resources, and shaping policies. Despite the importance of women’s voices and their empowerment in policy and decision-making processes, available metrics show that women’s policy and political empowerment remains low. Moreover, these metrics are inadequate in systematically tracking women’s voices and empowerment across different levels of decision-making. IFPRI developed an assessment framework—Women’s Empowerment in Agrifood Governance (WEAGov)—to assess women’s voices and empowerment in national policy processes in agrifood systems. This paper presents results from the pilot testing of WEAGov in India from January to March 2024. In this paper, we present how the WEAGov tool works in the Indian context, analyze trends in the data that we collected during the pilot, and provide an overview of the status of women’s voices and empowerment in the agrifood policy process as of March 2024. The pilot testing in India provides useful lessons on improving the measurement of these outcomes and offers valuable policy insights on critical entry points for increasing women’s voices and empowerment in the national agrifood policy process, design, implementation, and evaluation.